Monitoring Everyday Upper Extremity Function in Patients with Complex Regional Pain Syndrome: A Secondary, Retrospective Analysis from ncRNAPain - Gudrun-Karin Kindl; Ann-Kristin Reinhold; Fabiola Escolano-Lozano; Johannes Degenbeck; Frank Birklein; Heike L. Rittner; Karolin Teichmüller (Pain Research and Management)
Objective. Complex regional pain syndrome (CRPS) represents a rare complication following injury to a limb. The DASH questionnaire (disability of arm, shoulder, and hand) evaluates everyday arm function. We assessed the DASH and its subitems in comparison to patients with brachial plexus lesions or fracture controls, analysed it over time, and in relation to active range of motion (ROM), to determine patients’ impairment and trajectory. Methods. The dataset included 193 patients with upper extremity CRPS from the noncoding RNA (ncRNA) Pain cohort, 36 fracture controls, and 12 patients with traumatic brachial plexus lesions. For the clinical and psychological characterisation, questionnaires and a goniometer for the measurement of ROM were utilized. Thirty-three patients were followed up after approximately 2.5 years of guideline treatment. Results. CRPS patients had a similar mean DASH of 54.7 (standard deviation (S.D.) ±21) as brachial plexus lesion patients (M = 51.4, S.D. ± 16.1) but different significantly from fracture controls (M = 21.2, S.D. ± 21.1). Pain and older age were predictors of the DASH. Activities requiring force or impact on the arm, shoulder, or hand were mostly affected in patients with CRPS. After 2.5 years of standard treatment, the mean DASH score fell to 41.3 (S.D. ± 25.2), weakness in leisure activities was recuperated, pain feelings were lessened, and ROM, e.g., wrist flexion, recovered by 36°. Two-thirds of patients improved in both the DASH and the ROM. Conclusions. CRPS is as disabling as a complete loss of arm function in brachial plexus lesions and exhibits only partial recovery. Developing QuickDASH versions for CRPS patients could reduce the load of questions in clinical studies. It would be prudent to consider the unexpected age dependency of the DASH in future studies. This trial is registered with DRKS00008964.